Underreporting of congenital syphilis cases and its implications for infection: An integrative review (Research, Society and Development, 2023)
Objective: To analyze the aspects involved in the underreporting of congenital syphilis (CS) cases and their implications for the management and/or treatment of the infection. Methods: The searches took place between February and May 2023 in five databases, LILACS, Web of Science, Scopus, Medline and PubMed. The criteria for selecting the articles were that they were available in full, answered the guiding question and were in any language. Results: From the research carried out, 81 results were obtained, but only 6 articles met the criteria imposed. Under-reporting and/or non-treatment can lead to negative outcomes such as miscarriage, fetal death and motor, cognitive, neurological, visual and auditory sequelae. Treatment can also be hampered by under-reporting, as this can jeopardize the supply of medication and consequently treatment failure. Difficulties on the part of professionals in terms of notification are also portrayed in the studies, which compromises the data provided in the Notifiable Diseases Information System (SINAN), resulting in underreporting of CS cases, and making it difficult for government bodies to act with promotion, prevention and appropriate treatment actions. Conclusions: It can be concluded that the underreporting of CS has multiple causes and that failure to complete the notification form has a direct negative impact on maternal and child health.